Formulation of Pickering emulsions for the development of surfactant‐free sunscreen creams. (6th June 2021) - Bordes, Claire; Bolzinger, Marie‐Alexandrine; El Achak, Myriam; Pirot, Fabrice; Arquier, Delphine; Agusti, Géraldine; Chevalier, Yves
Abstract: Objective: Pickering emulsions are increasingly used in the pharmaceutical and cosmetic fields, especially for topical applications, since these systems require solid particles as emulsifiers instead of surfactants which are known to cause skin irritation. The solid inorganic nanoparticles (TiO2 and ZnO) used as UV filters in sunscreen formulations may also stabilize emulsion droplets, so that the utility of surfactants may be questioned. Surfactant‐free sunscreen emulsions solely stabilized by such nanoparticles (NPs) have been studied. Methods: The ability of these NPs to stabilize o/w emulsions containing a 'model' oil phase, the C12 ‐C15 alkylbenzoate, has been assessed. ZnO and hydrophilic silica‐coated TiO2 NPs widely used in sunscreen products were used together with their mixtures. The emulsification efficiency, the control of droplet size and the stability of o/w Pickering emulsions solely stabilized by NPs were investigated. A ZnO/TiO2 NPs mixture characterized by a theoretical SPF of 45 was finally used as unique emulsifiers to develop a surfactant‐free sunscreen emulsion. Results: Stable Pickering emulsions containing 10 up to 60 wt% of C12 ‐C15 alkyl benzoate were formulated with 2 wt% ZnO in the aqueous phase. The droplet size was controlled by the solid NPs content with respect to oil and the emulsification process. Hydrophilic TiO2 NPs did not allow the stabilization of emulsions. The substitution of TiO2 for ZnO up to 60–70 wt% in a 20/80 o/w emulsion was successfully performed. Finally, a ZnO/TiO2 NP mixture was tested as unique emulsifier system for the formulation of a sunscreen cream. Despite a lower viscosity, the obtained Pickering emulsion was stable and exhibited a photoprotective effect similar to the corresponding surfactant‐based sunscreen cream with an in vitro SPF of about 45. Conclusion: Surfactant‐free Pickering emulsions can be stabilized by the UV‐filter nanoparticles for the manufacture of sunscreen products. Resume: Objectifs: Les émulsions de Pickering sont de plus en plus utilisées dans les domaines pharmaceutique et cosmétique, notamment pour les applications topiques, car ces systèmes utilisent des particules solides comme émulsifiants au lieu de tensioactifs qui sont connus pour provoquer des irritations cutanées. Les nanoparticules inorganiques solides (TiO2 et ZnO) utilisées comme filtres UV dans les formulations d'écran solaire peuvent également stabiliser les gouttelettes d'émulsion, de sorte que l'utilité des tensioactifs peut être remise en question. Des émulsions de protection solaire sans tensioactifs et uniquement stabilisées par de telles nanoparticules (NP) ont été étudiées. Méthodes: La capacité de ces NP à stabiliser les émulsions H/E contenant une phase huileuse «modèle», le benzoate d'alkyle C12 ‐C15, a été évaluée. Des NP de ZnO et de TiO2 couvert de silice hydrophile, que l'on trouve largement dans les produits de protection solaire, ont été utilisées séparément et en mélange. L'efficacité d'émulsification, le contrôle de la taille des gouttelettes et la stabilité des émulsions de Pickering H/E uniquement stabilisées par les NP ont été étudiés. Un mélange de NP ZnO/TiO2 caractérisé par un SPF théorique de 45 a finalement été utilisé comme émulsifiant unique pour développer une émulsion de protection solaire sans tensioactif. Résultats: Des émulsions de Pickering stables contenant 10 à 60% en poids de benzoate d'alkyle C12 ‐C15 ont été formulées avec 2% en poids de ZnO dans la phase aqueuse. La taille des gouttelettes était contrôlée par la teneur en NP solides par rapport à l'huile et le procédé d'émulsification. Les NP de TiO2 hydrophile n'ont pas permis la stabilisation des émulsions. La substitution des NP de TiO2 par du ZnO jusqu'à 60–70% en poids dans une émulsion 20/80 H/E a été réalisée avec succès. Enfin, un mélange de NP ZnO/TiO2 a été testé en tant que système émulsifiant unique pour la formulation d'une crème solaire. Malgré une viscosité plus faible, l'émulsion de Pickering obtenue était stable et présentait un effet photoprotecteur similaire à la crème solaire à base de tensioactif correspondante avec un SPF in vitro d'environ 45. Conclusion: Les émulsions Pickering sans tensioactifs peuvent être stabilisées par les nanoparticules de filtre UV pour la formulation de produits de protection solaire.